Teachers Perception of Learner Autonomy in Senior High School (RETAIN, 2018)
Abstract The purpose of this study was to describe teachers’ perception about learner autonomy in senior high school. This study was designed as a qualitative research. In doing so, four English teachers in senior high school were interviewed to identify their further general perceptions towards learner autonomy. In this study the researcher used unstructured interview and open ended question to gain the data. The finding has shown that the teachers have a good understanding in learner autonomy principles, a various understanding about the teachers’ practices in offering autonomous learning and a rich understanding in explaining the challenges in helping the learners become more autonomous. Keywords: teachers, perception, learner autonomy Abstrak Tujuan dari penelitian ini adalah untuk menjelaskan pemahaman guru tentang otonomi pelajar di sekolah menengah atas. Penelitian ini dirancang sebagai penelitian kualitatif. Dengan demikian, empat guru bahasa Inggris di sekolah menengah atas diwawancarai untuk mengidentifikasi persepsi umum mereka lebih lanjut terhadap otonomi pelajar. Dalam penelitian ini peneliti menggunakan wawancara tidak terstruktur dan pertanyaan terbuka untuk mendapatkan data. Temuan ini menunjukkan bahwa para guru memiliki pemahaman yang baik dalam prinsip otonomi pelajar, berbagai pemahaman tentang praktik guru dalam menawarkan pembelajaran otonom dan pemahaman yang kaya dalam menjelaskan tantangan dalam membantu peserta didik menjadi lebih otonom. Kata kunci: guru, persepsi, otonomi pembelajar